Effect of ribavirin on zidovudine efficacy and toxicity in vitro: A concentration-dependent interaction - Sim, S.M.; Hoggard, P.G.; Sales, S.D.; Phiboonbanakit, D.; Hart, C.A.; Back, D.J. (1998)
Zidovudine (ZDV) is converted to its active triphosphate (ZDVTP) by intracellular kinases, The intermediate ZDV monophosphate (ZDVMP) is believed to play a major role in ZDV toxicity. Manipulation of ZDV phosphorylation is a possible therapeutic strategy for altering the risk-benefit ratio, Here we investigate whether combining REV with ZDV is able to modulate efficacy and toxicity of ZDV, We have measured the intracellular activation of ZDV (0.3 mu M) in the absence and presence of ribavirin (RBV; 2 and 20 mu M) in Molt 4 and U937 cells. MTT cytotoxicity of ZDV (10-1000 mu M) was also measured with and without REV (2 mu M) in Molt 4 and U937 cells, Measurement of endogenous deoxythymidine triphosphate (dTTP) allowed investigation of the dTTP/ZDVTP ratio. The antiviral efficacy of ZDV in combination with REV (2 mu M) was assessed by HIV p24 antigen measurements. In the presence of REV (2 and 20 mu M) a decrease in total ZDV phosphates was observed, owing mainly to an effect primarily on ZDVMP rather than the active ZDVTP, REV also increased endogenous dTTP pools in both cell types, resulting in an increase in the dTTP/ZDVTP ratio. ZDV alone significantly reduced p24 antigen production, with an IC50 Of 0.34 mu M Addition of REV increased the IC50 approximately fivefold (1.52 mu M) However, at higher concentrations of ZDV (10 and 100 mu M) the antagonistic effect of REV (2 mu M) on ZDV was lost, The REV-mediated decrease in ZDVMP may explain the reduction in ZDV toxicity when combined with RBV (2 mu M). Cytotoxicity of ZDV was reduced in the presence of REV (2 mu M) at all concentrations in both cell lines, probably owing to saturation of ZDVTP formation. The interaction of ZDV and REV is concentration dependent.